Full-length TDP-43 and its C-terminal domain form filaments in vitro having non-amyloid properties. (2nd January 2021) - Capitini, Claudia; Fani, Giulia; Vivoli Vega, Mirella; Penco, Amanda; Canale, Claudio; Cabrita, Lisa D.; Calamai, Martino; Christodoulou, John; Relini, Annalisa; Chiti, Fabrizio
Abstract: Accumulation of ubiquitin-positive, tau- and α-synuclein-negative intracellular inclusions of TDP-43 in the central nervous system represents the major hallmark correlated to amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with ubiquitin-positive inclusions (FTLD-U). Such inclusions have variably been described as amorphous aggregates or more structured deposits having amyloid properties. Here we have purified full-length TDP-43 (FL TDP-43) and its C-terminal domain (Ct TDP-43) to investigate the morphological, structural and tinctorial features of aggregates formed in vitro by them at pH 7.4 and 37 °C. AFM images indicate that both protein variants show a tendency to form filaments. Moreover, we show that both FL TDP-43 and Ct TDP-43 filaments possess a largely disordered secondary structure, as ascertained by far-UV circular dichroism and Fourier transform infra-red spectroscopy, do not bind Congo red and induce a very weak increase of thioflavin T fluorescence, indicating the absence of a clear amyloid-like signature.